Journal Effect of Workload, Work Environment and Work Motivation on Employee Performance of Pt. Merak Jaya Beton Pamotan, Sidoarjo - Agus Rohmana (LPPM NAROTAMA UNIVERSITY, Indonesia, 2022)
This research has a goal in the problem is whether the workload, work environment and work motivation have a simultaneous effect on the performance of employees of PT. Merak Jaya Plan Pamotan Sidoarjo. The population used is all employees of PT Merak Jaya Beton Plan Pamotan Sidoarjo in the Trucking Management System department, totaling 54 employees using non-probability or non-random sample selection. The data analysis method used is Multiple Linear Regression with the help of SPSS. The results showed that (1) partially the workload variable had a significance value of 0.040 <0.05 the workload variable had a partially significant effect on the employee performance variable. (2) partially the work environment variable has a significance value of 0.708 > 0.05, meaning that the work environment variable partially has no significant effect on employee performance variables. (3) partially the work motivation variable has a significance value of 0.080 > 0.05, meaning that the work motivation variable partially has no significant effect on the employee performance variable.